Inuit hunters, Saami herders, and lessons from the Amadjuak experiment (Baffin Island, Canada) - Laugrand, Frédéric (Publications scientifiques du Muséum, 2022)
In 1920-21, reindeer and Saami herders from Norway are sent to Baffin island on board the Nascopie. The Canadian Government not only hoped to make a lucrative business but also to introduce herding among the Inuit, assuming that reindeer and caribou both belong to the same species (Rangifer tarandus). But for various reasons, the Amadjuak experiment turned into a failure. Many reindeer died and Saami and their families decided to abandon the place. As for the Inuit, they helped the Saami but they showed no interest in becoming herders. They rather preferred their hunting and nomadic life. This paper explores the reasons of this lack of interest and its ontological foundations. For the Inuit caribou remain ambiguous animals: they are an ideal prey, they have to be hunted, but have to be respected so they can reproduce. They are also connected to the earth, the deceased and the ijirait, mountain spirits. Sometimes they are associated with an owner, they cannot be domesticated at a large scale nor dominated. On the basis of this ethnography the discussion between Ingold, Willerslev and Vitebsky on sacrifice as the ideal hunt is not very helpful to understand their practises. Chasseurs Inuit, éleveurs Saami et les leçons de l’expérience d’Amadjuak (île de Baffin, Canada)En 1920-21, des rennes et des éleveurs saami de Norvège sont envoyés en Terre de Baffin à bord du navire de la Compagnie de la Baie d’Hudson, le Nascopie. Le gouvernement canadien espère non seulement réaliser une affaire lucrative, mais enseigner l’élevage du renne aux Inuit partant du principe que renne et caribou sont un même animal (Rangifer tarandus). Un peu partout en Amérique du Nord, en effet, comme en Alaska ou au Labrador, certains gouvernements imaginent ainsi régler, entre autres, le problème des famines récurrentes liées au cycle de vie du caribou. En Alaska, en particulier sur la péninsule de Seward, les expériences semblent fonctionner et des familles de Saami s’installent. Pour de multiples raisons, les résultats ne sont toutefois ...